2011
DOI: 10.1590/s0103-05822011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Composição de lancheiras de alunos de escolas particulares de São Paulo

Abstract: OBJETIVO: Avaliar qualitativamente a composição das lancheiras de crianças do segundo ao quinto ano do ensino fundamental de escolas privadas de São Paulo. MÉTODOS: O delineamento do estudo foi transversal e a coleta de dados foi realizada em cinco unidades de uma rede particular de ensino, localizadas em regiões distintas da Grande São Paulo. A observação dos lanches ocorreu em três dias não consecutivos do ano de 2008 para cada criança. A amostra foi constituída pela totalidade de crianças do segundo ao quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
0
2
0
15
Order By: Relevance
“…Matuk et al 19 found that 51% of preschooler lunchboxes were filled with crackers, cookies, and cakes, 20% with sweets, snack chips, and fried foods, and 35% with cold cuts. Corroborating these data, a research conducted in a Brazilian private school revealed that stuffed cookies were the most common (33%) food in children's lunchboxes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Matuk et al 19 found that 51% of preschooler lunchboxes were filled with crackers, cookies, and cakes, 20% with sweets, snack chips, and fried foods, and 35% with cold cuts. Corroborating these data, a research conducted in a Brazilian private school revealed that stuffed cookies were the most common (33%) food in children's lunchboxes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Trata-se de um produto não perecível, de embalagem prática que permite com que as crianças consigam facilmente abrir e consumir sozinhas, tornando-se uma opção viável para um lanche rápido, trazendo saciedade por possuir cereal e fibra (MATUK et al, 2011). Porém, nem sempre esta é a melhor opção quando se trata de açúcar e gordura.…”
Section: Methodsunclassified
“…Often, what is observed in studies evaluating the quality of intermediate snacks in preschoolers and schoolchildren is a high presence of industrialized foods, although eventually they follow the recommendation of food groups. Foods such as snacks, cereal, cereal bar, stuffed biscuit, biscuit without filling, artificial juices like nectar, industrialized cake, milk drink, yogurt with added sugar, processed cheese and candies are common in children's snacks, 54 and reflect inadequate practices that reinforce the maintenance of the nutritional status profile of children today.…”
Section: The Consumption Profile Of Children Under 5 Years Old In Brazilmentioning
confidence: 99%